Tokenization and the future of property investment: A new paradigm for real estate - El Jaouhari, Asmae; Samadhiya, Ashutosh; Kumar, Anil; Chokshi, Hemakshi; Šešplaukis, Audrius; Raslanas, Saulius (International Journal of Strategic Property Management, 2025)
Tokenization has improved liquidity, access to markets and ownership models for real estate investments. This research aims to analyze applications, enablers and challenges of tokenization by conducting a systematic literature review of 75 peer-reviewed journal articles that discuss real estate tokenization using the Technology-Organization-Environment (TOE) framework. The findings show that tokenization allows more efficient markets with automation, transparency, and liquidity; new investment methods in real estate, such as crowdfunding and fractional ownership; and reductions of any limits of traditional real estate through the reduction of costs, faster transactions, and higher investor engagement. Nevertheless, there are still barriers to real estate tokenization including technological risks, regulatory fragmentation, and the reluctance of organizations towards decentralized asset structures. These are supported by the literature review findings. These barriers highlight the necessity of investor education, technology standardization, and regulatory harmonization with the aim of promoting wider adoption. This paper lays the groundwork for future research into risk management, scalability, and institutional integration of real estate tokenization by highlighting important gaps in existing literature and consolidating previous studies. Ultimately, even though tokenization has a lot of potential to change the real estate market, its long-term success depends on the development of accurate legal frameworks and the seamless incorporation of tokenized assets into conventionnel financial systems.